2019
DOI: 10.1016/j.jmatprotec.2019.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of AA2XXX/AA7XXX friction stir welds

Abstract: Comparable microstructures and mechanical properties are obtained for the different AA2139-T8/AA7020-T651 joints welded in the range 600-1000 rev. min −1 / 250-550 mm.min −1 as rotation and advance speeds. Joints exhibit tensile properties as good as 77%-79% of the yield strength and 88%-96% of the ultimate tensile strength of the AA7020 base material. Except for the high speed conditions that failed in the nugget, all joint variants failed in the heat affected zone (HAZ), which is also consistent with lower h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The ECAP process was performed using a split die shown in Figure 1 in which the two parts of the channel intersected with an internal channel angle of ϕ = 120 • and with an additional outer corner angle of ψ = 20 • . The die geometry imposed an equivalent strain of about 0.65 per pass according to Equation (1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ECAP process was performed using a split die shown in Figure 1 in which the two parts of the channel intersected with an internal channel angle of ϕ = 120 • and with an additional outer corner angle of ψ = 20 • . The die geometry imposed an equivalent strain of about 0.65 per pass according to Equation (1).…”
Section: Methodsmentioning
confidence: 99%
“…Aeronautical, terrestrial and marine transport applications are faced with extreme lightweight design requirements. Aluminum alloys are ideal materials for these purposes because they have good mechanical properties at relatively low densities [1,2]. Because of their high mechanical performances, the aluminum alloys 7xxx and 2xxxx series are widely used for aerospace, automotive and defense structural parts in many different structural elements [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The microscopic observations showed that there was no real mixing of the materials was achieved. Only a small amount of material from one side is moved onto the other side of the nugget [ 18 ]. Various zones can be observed in the weld, which is the effect of the temperature gradient across the weld cross-section and the large uniform deformation [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…The input parameters required to produce a welded joint by the FSW welding process are tool rotation speed, translational tool speed or welding speed, axial force, immersion depth, tool angle, geometry and characteristics of the tool shoulder and tool pin [ 12 ]. Numerous studies have been performed in the field of the influence of FSW welding parameters on the mechanical properties and microstructure of the welded joint [ 13 , 14 , 15 , 16 , 17 , 18 ]. An optimal ratio between tool rotation speed and welding speed n / v is required to guarantee good material mixing and heat input along the entire length of the welded joint [ 19 ].…”
Section: Introductionmentioning
confidence: 99%